1998
DOI: 10.1021/bi981593h
|View full text |Cite
|
Sign up to set email alerts
|

Key Role of Phenylalanine 20 in Cytochrome c3:  Structure, Stability, and Function Studies

Abstract: Aromatic residues in c-type cytochromes might have an important function in the folding and/or electron transferring properties of the molecule. In the tetraheme cytochrome c3 (Mr 13 000) from Desulfovibrio vulgaris Hildenborough, Phe20, is located between heme 1 and heme 3 with its aromatic ring close and almost parallel to the ring plane of heme 1. We replaced this residue by a nonaromatic hydrophobe residue, leucine, and analyzed the effects in terms of functional, structural, and physicochemical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 34 publications
3
15
0
Order By: Relevance
“…7). Aromatic residues such as Phe residues have been shown to have an important function in the folding and/or electron transferring properties of proteins [37]. This is important in relation to the putative redox functions suggested for Ngb [10].…”
Section: Discussionmentioning
confidence: 93%
“…7). Aromatic residues such as Phe residues have been shown to have an important function in the folding and/or electron transferring properties of proteins [37]. This is important in relation to the putative redox functions suggested for Ngb [10].…”
Section: Discussionmentioning
confidence: 93%
“…1, the ArAT Ph structure is more compact due to shortened loops (colored in green) compared to those observed in thermophilic ( Thermus thermophilus , PDB ID: 1bjw) and mesophilic ( E. coli , PDB ID: 1ars). According to the thermodynamic database of proteins and mutants (ProTherm; http://gibk26.bse.kyutech.ac.jp/jouhou/protherm/protherm.html) [32], the highest T m of an enzyme measured directly by DSC was 121.6 °C for cytochrome c 3 from Desulfovibrio vulgaris [33], although the T m value of Ph CutA1 from P. horikoshii was reported recently to be 150 °C [34] .…”
Section: Structural Elements Responsible For Thermostability: Increasmentioning
confidence: 99%
“…In the case of DvHc 3 , in which F20 was also replaced by leucine, it was shown that the macroscopic redox potentials were globally affected [38]. Moreover, it was proposed by the authors that the intramolecular electron exchange between heme III and heme I was drastically affected by the F20L replacement [38]. In the highly homologous tetraheme cytochrome DvMc 3 , the roles of aromatic residues in Table 2 Heme geometry for PpcAF15L (this work) and PpcA [20] cytochromes in solution.…”
Section: Heme Reduction Potentials and Redox Interactionsmentioning
confidence: 69%
“…The structural motif formed by F15 and hemes I and III is also conserved in the tetraheme cytochrome c 3 family, in which F20 occupies an equivalent position. There are biochemical studies reported for F20 mutants of D. vulgaris tetraheme cytochromes c 3 isolated from the strains Hildenborough (DvHc 3 ) and Miyazaki (DvMc 3 ) [38][39][40]. In the case of DvHc 3 , in which F20 was also replaced by leucine, it was shown that the macroscopic redox potentials were globally affected [38].…”
Section: Heme Reduction Potentials and Redox Interactionsmentioning
confidence: 99%
See 1 more Smart Citation